How Blockchain can be used for Verifying the Authenticity of Video/Image (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
With the explosive advancement of modern technology we heavily rely upon digital data in the form of video and image. Digital content has been the norm for quite a few years in all aspects of modern society for ease of use and conveniences. Relevant visual information may be utilised in a range of settings, such as the media, law enforcement, publications, legal procedures, medical imaging, the military, and consumer museums. Though the development of advanced technology with the help of sophisticated artificial intelligence(AI) algorithms have opened the door to temper digital data and contents. [1] This misinterpretation of advanced technology has made the integrity of the video/image file questionable. [2] In the context of using the video/image file in court or any other places for presenting proof have been disputable. In thisresearch article I present a framework for verifying the authenticity of video/image using blockchain technology. Using this framework the deep-fake problems can be countered and a layer of trust can be established verifying the integrity of the visual contents. The IoT device capturing the image or video file computes a hash before the data leaves the device. Then the hash is stored in a blockchain system to provide a transparent way to check the integrity of the file.